Galectin-3 Promotes Müller Glia Clearance Phagocytosis via MERTK and Reduces Harmful Müller Glia Activation in Inherited and Induced Retinal Degeneration - Lew, Deborah S.; McGrath, Morgan J.; Finnemann, Silvia C. (Frontiers in Cellular Neuroscience, 2022)
Clearance phagocytosis is a documented function of Müller glia in the retina. However, the molecular mechanisms of Müller glia phagocytosis remain largely undefined. Here, we show that extracellular galectin-3 and protein S promote clearance phagocytosis by immortalized human MIO-M1 Müller cells in an additive, saturable manner. Galectin-3 promotes phagocytosis by primary Müller glia from wild-type (WT) mice but not from mice that lack the engulfment receptor MERTK and therefore develop postnatal photoreceptor degeneration. Probing a possible functional link between Müller galectin-3 and MERTK, we discovered that mertk-/- Müller glia in situ show excess galectin-3 at postnatal day 20 (P20), an age prior to detectable photoreceptor degeneration. Moreover, double knockout (DKO) mice lacking both galectin-3 and MERTK show increased activation of Müller cells (but not of microglia) at P20 and more pronounced photoreceptor loss at P35 compared to mice lacking MERTK alone. Exploring the well-established sodium iodate injury model, we also found more severe activation specifically of Müller glia and worse retinal damage in mice lacking galectin-3 compared to WT mice. Indeed, galectin-3 deficiency significantly increased sensitivity to injury, yielding Müller activation and retinal damage at a sodium iodate concentration that had no effect on WT retina. Altogether, our results from both inherited and acutely induced models of retinal degeneration agree that eliminating galectin-3 exacerbates Müller cell activation and retinal degeneration. These data identify an important protective role for the MERTK ligand galectin-3 in the retina in restraining Müller glia activation.